Wall constructions (load bearing wall) / Mohamad Nor Fakhrurrazi Hadzir - Hadzir, Mohamad Nor Fakhrurrazi (Universiti Teknologi MARA, Perak, 2022)
Walls is very important structure in buildings. It have many function such as, to enclose, divide and separate the area, to provide shelter and protection from weather and also to provide privacy for the people living in it. This report will discuss about wall construction for the load bearing wall of the building. This report was conducted for the construction of one storey house at Jalan Rumbia, Kampung Sijangkang, Telok Panglima Garang, Selangor Darul Ehsan. The objective of this report is the whole process and method for wall construction for load bearing wall. It is also focus on how many time it take to complete the wall construction. This report also look at the problem occurred and solution taken in wall constructions.